Recovery of β-Lagtoglobulin from whey using combination of size exclusion chromatography and ion exchange chromatography techniques - Muhammad Fuad, Abdullah (2010)
Variety of proteins exists in bovine whey such as a-lactalbumin (a-lac), β-lactoglobulin, (β-lg), bovine serum albumin (BSA) and immunoglobulin. The value for each individual protein can be raised if it can be isolates into a single and pure protein form. Individual whey protein hasnumerous potential applications in pharmaceutical, nutraceutical and food industry. In the current study, a series of chromatographic technique was used to recover the most abundant whey protein, β-lg from the whey. In the first step, whey was separated based on it size using size exclusion chromatography (SEC). Superdex200 and Superdex75 columns were tested for SEC experiment. Superdex75 showed better peak separation compared to the Superdex200 for whey fractionation. Further polishing step was done using 1 ml HiTrap Q-Sepharose anion exchange column to fully separate a-lac and β-lg protein fraction. Different linear salt elution gradient at 5 columns volume (CV) and 10 CV were studied. I 0 CV linear salt gradient protocol gives a better separation resolution between a-lac and β-lg mixture with some fraction contain mainly pure β-lg. Recovery of single β-lg from whey can added the value of the whey-based product and it can be used for specific application.